Case Report: Endocapillary Glomerulopathy Associated With Large Granular T Lymphocyte Leukemia - Zhao, Tao; Hu, Nan; Yu, Xiaojuan; Su, Tao (Frontiers in Immunology, 2022)
Large granular T lymphocyte leukemia (T-LGLL) is a rare indolent lymphocyte leukemia. The clonal proliferation of T cells, which is related to STAT3 gene mutation and abnormal Fas-mediated apoptosis pathway after cell activation, plays a major role in disease progression. Some studies have found that the exogenous and continuous stimulation of endogenous antigens, such as virus infection, is related to the pathogenesis of T-LGLL. The renal pathological manifestations of T-LGLL have rarely been described. In this study, we report a case of T-LGLL with kidney involvement as proteinuria, acute kidney injury, with the appearance of circulating T-LGL infiltrating intra-glomerular capillaries, and endocapillary glomerulopathy. We also summarize reported cases of renal injury associated with LGLL.